The Influence of Job demand On Burnout with Job Resource and Personal Resource as moderator: Study on PT Kusumaputra Santosa Karanganyar - Ardianti Nur Oktarina; Mugi Harsono (Sebelas Maret Business Review, 2016)
The aim of this research was to analyse the effect of job demand on burnout and to analyse the moderators (job resource and personal resource) effect on the relationship between job demand and burnout. This research used quantitative research method with 232 peoples sample respondents. Data analysis techniques were using multiple linear regression and MRA (Moderating Regression Analysis) to determine the effect of moderators. The results of this research are follows: 1) Job demand has a significant positive effect on burnout, and tested on every Job demand dimensions (Qualitative demand, quantitative demand, and organizational demand) positively affects burnout significantly. 2) Job resources become moderation predictor of job demand on burnout. Meanwhile, when tested on every dimension of job demand (Qualitative demand, quantitative demand, organizational demand), then can be concluded Job resource becomes moderation quasi in qualitative demand on burnout, and job resource becomes moderation predictor in quantitative demand on burnout, job resource becomes moderation predictor in organizational demand on burnout. 3) Personal resources become moderation predictor between job demand on burnout. Meanwhile, when tested on every dimension of job demand (Qualitative demand, quantitative demand, organizational demand), then showed Personal Resource becomes moderation quasi on qualitative demand on burnout, and Personal resource becomes moderation predictor in quantitative demand on burnout, Personal resource becomes moderation predictor in organizational demand on burnout.